The Effect of Different Dose of Drop Jumping on Symptoms of Muscle Damage - Albertas Skurvydas; Gediminas Mamkus; Dalia Mickevičienė; Diana Karanauskienė; Dovilė Valančienė; Mantas Mickevičius; Sigitas Kamandulis (Lithuanian Sports University, 2018)
Background. The aim of this study was to follow symptoms of exercise induced muscle damage in response to 50, 100 and 200 drop jumps with maximal intensity. Methods. Three groups of young healthy men (n = 10 in each group) performed a bout of mechanically demanding stretch shortening cycle exercise consisting of 50, 100 and 200 drop jumps. Voluntary and electrically induced knee extension torque, creatine kinase, muscle soreness were measured before and 24 h after exercise. Results. Indirect symptoms of exercise induced damage were dependent on DJs volume: the higher the numbersof jumps, the more symptoms were observed. Only after 200 DJs compared to 50-100 DJ there was decrease of CAR and H of DJ, and 24 h after 200 DJs CK was greater than after 50-100 DJs. Conclusion. In response to acute severe muscle-damaging exercise (after 200 DJs), indirect symptoms of exercise-induced muscle damage occurred. Keywords: stretch-shortening cycle exercise, motor fatigue, muscle soreness, muscle torque.